Synthesis, characterization and thermal behaviour of heavy trivalent lanthanide malonates - Locatelli, J. R.; Carvalho, C. T.; Caires, Flavio J. [UNESP]; Ionashiro, Massao [UNESP] (Editora Unesp, 2010)
Compostos Ln-L no estado sólido, em que Ln representa os lantanídeos trivalentes (Tb - Lu) e L é malonato, foram sintetizados neste trabalho. A termogravimetria e análise térmica diferencial simultânea (TG-DTA), calorimetria exploratória diferencial (DSC), difratometria de raios X pelo método do pó, espectroscopia na região do infravermelho (FTIR), TG-FTIR, análise elementar e complexometria foram utilizadas para caracterizar e estudar o comportamento desses compostos. A desidratação desses compostos começa em 303 K e os compostos anidros são estáveis até 548 K. Os resultados também proporcionaram informações com respeito à denticidade do ligante, comportamento térmico e a identificação de alguns produtos gasosos eliminados durante a decomposição térmica desses compostos.

Solid-state Ln-L compounds, where Ln stands for heavy trivalent lanthanides (Tb-Lu) and L is malonate, have been synthesized. Simultaneous thermogravimetry and differential thermal analysis (TG-DTA), differential scanning calorimetry (DSC), X-ray powder diffractometry, infrared spectroscopy, TG-FTIR system, elemental analysis and complexometry were used to characterize and to study the thermal behaviour of these compounds. The dehydration of the compounds begins at 303 K and the anhydrous compounds are stable up to 548 K. The results also provided information concerning the ligand's denticity, thermal behaviour and identification of some gaseous products evolved during the thermal decomposition of these compounds.
Keywords: lantanídeos pesados; malonato; comportamento térmico; heavy lanthanides; malonate; thermal behaviour